Impact Analysis of the Use of Biotechnology, Agricultural Wastewater Treatment, and Government Policies on the Sustainability of Organic Agriculture in East Java - Suryandari, Ratnawati Yuni; Karma, Karma; Sutrisno, Eko; Suparwata , Dewa Oka (West Science Interdisciplinary Studies, 2025)
This study examines the impact of biotechnology adoption, agricultural wastewater treatment, and government policies on the sustainability of organic agriculture in East Java, Indonesia. Using a quantitative approach, data were collected from 65 respondents through a Likert scale (1-5) questionnaire and analyzed using SPSS version 25. The results indicate that biotechnology adoption, effective wastewater treatment, and supportive government policies significantly enhance the sustainability of organic agriculture, with regression coefficients of 0.42, 0.35, and 0.38, respectively. The findings highlight the importance of integrating advanced technologies, improving resource management, and strengthening policy frameworks to promote sustainable farming practices. This study provides actionable insights for farmers, policymakers, and researchers aiming to enhance the sustainability of organic agriculture in East Java and beyond.